Critical Making Workshops: Sparking Meta-Discussions for Critical Thinking in Vocational Education - Sipos, Regina; Kutschera, Alexander; Klose, Janina (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
This article explores how critical making - or a combination of critical thinking and making - could enhance and future-proof technical and vocational education and training (TVET). The article reports from a series of multi-stakeholder participatory workshops with educators, caretakers, pupils and makers. The workshops themselves represent an example of critical making, hereby providing the participants with an immediate understanding of the concept. Through discussions, the stakeholders mapped the viability, challenges and opportunities for a successful implementation of critical making into German curricula. The paper ends with reflections on the general difficulties of updating a curriculum and proposes a workaround: complementing the technical approach of the existing TVET curriculum with maker tools to foster digital skills and meta-level discussions to foster critical thinking.